Postsynthetic Modification of Metal−Organic Frameworks for Photocatalytic Applications. Issue 5 (12th May 2022) - Lin, Huaxing; Xu, You; Wang, Bing; Li, Dong-Sheng; Zhou, Tianhua; Zhang, Jian
Abstract : Postsynthetic Modification of Metal–Organic Frameworks In article number 2100176, Tianhua Zhou, Jian Zhang, and co‐workers, discuss the recent development of functionalized metal‐organic frameworks throught post‐synthetic modification (PSM) of metal nodes, organic ligand, pore and surface toward photocatalytic water splitting, CO2 reduction, organic transformation, and degradation of water pollutants. The challenges and perspectives on PSM of MOFs for photocatalysis are also described and discussed.